2021
DOI: 10.3390/cells10112931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunomodulatory Responses and Changed Wound Healing in Type 2 Diabetes—A Study Exploiting Dermal Fibroblasts from Diabetic and Non-Diabetic Human Donors

Abstract: The dermis is the connective layer between the epidermis and subcutis and harbours nerve endings, glands, blood vessels, and hair follicles. The most abundant cell type is the fibroblast. Dermal fibroblasts have a versatile portfolio of functions within the dermis that correspond with different types of cells by either direct contact or by autocrine and paracrine signalling. Diabetic skin is characterized by itching, numbness, ulcers, eczema, and other pathophysiological changes. These pathogenic phenotypes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“… 3 Studies have shown that the pathogenic phenotype leading to chronic inflammation in diabetic wounds is associated with the effects of the reactive glucose metabolite methylglyoxal, 15 AGEs, 16 and migration inhibitor (MIF) on dermal cells. 6 Dermal fibroblasts from diabetic donors exhibited insulin-induced decreased glucose uptake and reduced insulin receptor expression.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“… 3 Studies have shown that the pathogenic phenotype leading to chronic inflammation in diabetic wounds is associated with the effects of the reactive glucose metabolite methylglyoxal, 15 AGEs, 16 and migration inhibitor (MIF) on dermal cells. 6 Dermal fibroblasts from diabetic donors exhibited insulin-induced decreased glucose uptake and reduced insulin receptor expression.…”
Section: Introductionmentioning
confidence: 97%
“… 3 Long-term hyperglycemia promotes the activation of NF-κB, 4 leading to chronic inflammation 5 and impairing skin fibroblast activation. 6 Difficult healing of foot ulcers in diabetes is a complex problem in clinical diseases. However, the treatment of refractory diabetic foot ulcers is insufficient, and better therapeutic interventions are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidermis becomes thick with overgrowth of the stratum corneum containing immature keratinocytes and alternated expression of tight junction proteins like claudin-1 and zonula occludens-1 (Yoshida et al 2001 ; Pummi et al 2001 ). A large number of cytokines and chemokines have been proposed to contribute to the pathogenesis of psoriasis (Nickoloff et al 2007 ). In this context, an increased transcript level of pro-inflammatory factors such as IL-6 is the essential hallmark of the disease (Grossman et al 1989 ; Fujishima et al 2010 ; Johnston et al 2013 ) in addition to further described cytokines important in psoriasis pathogenesis such as TNF-alpha, IL-22 and IL-17 (Zheng et al 2007 ; Nickoloff 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their role in extracellular matrix production and scar tissue formation, fibroblasts release cytokines to provide regulatory control over immune cell function 1 . Dermal fibroblasts basally secrete tumour necrosis factor alpha (TNF-α), interferon gamma, interleukin-6 (IL-6) and IL-12, with elevated secretions in response to stimuli such as histamine and bacterial lipopolysaccharide (LPS) 2 , 3 . The release of cytokines by wound fibroblasts during inflammation leads to the activation of nearby immune cells 1 .…”
Section: Introductionmentioning
confidence: 99%